A Methodological Approach and Conceptual Tools for Studying Migrant Belongings in African Cities: A Case of Zimbabweans in Johannesburg - Chereni, Admire (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2013)
Many scholars view the relaxation of restrictions to enter and reside in South Africa after the end of apartheid in 1994 as a catalyst for a number of changes in regional human migration. In this article, I show that human migration dynamics in post-apartheid South Africa pose theoretical and methodological challenges for studies of belonging among migrants. I argue that the majority of studies of belonging among migrants in South Africa rely on nation-state frames of reference and quantitative approaches. Furthermore, they largely seek to establish general patterns of migration processes. While these studies illuminate macro-level factors which seemingly structure migration experiences, they provide only a partial picture of migration dynamics. Often, they fail to sufficiently attend to context-dependent modes of emplacement among migrants in the urban zones due to the conceptual and methodological tools they use. The purpose of this article, therefore, is to suggest theoretical assumptions, concepts and methodological tools which constitute an alternative design for studying social constructions and practices of belonging among migrants in post-apartheid South Africa. The article draws on my doctoral research of Zimbabweans in Johannesburg for illustrations. URN: http://nbn-resolving.de/urn:nbn:de:0114-fqs140163